SUICIDE IN ADULT MAN : A CASE REPORT AND FORENSIC MEDICAL ASPECTS - WAHYU DWI ATMOKO; NIUFTI AYU DEWI MAHILA (LP2MTBM MAKARIOZ, 2023)
Hanging is a condition in which there is a constriction of the neck by a snarer caused by all or part of the body's weight. Hanging is a way of death often found in suicides and is a mechanism of death that usually occurs. In December 2022, a man was found dead who allegedly hanged himself in the Mojo Cemetery, Jebres, Surakarta. The positioning body is hanging with a black raffia rope on a teak tree branch of approximately 1 meter. During the TKP investigation, investigators found several pieces of evidence in the form of identification cards, family cards, wills, and letters of loan installments. An external post-mortem examination was carried out and found sliding abrasions and circular pressure on the neck from front to back, due to blunt force, as well as signs of asphyxia or suffocation. The exact cause of death is unknown because an internal examination was not carried out at the investigator's request. The time of death was estimated at two to eight hours before the examination.